(untitled) (The Pakistan Development Review, 2007)
Better rule of law would generate economic growth, which would in turn build constituencies for democratic reforms [Root and May (2006)]. Consider prisoners dilemma, to Law and Economics Scholars, the inevitability of prisoner’s dilemmas arising to block potentially efficient exchanges explains the need for and consequently the adoption of contract law. When the law enforces contracts, it permits the participants in a potential prisoners’ dilemma the option of escaping the dominant strategy equilibrium of non-cooperation, which prevents the achievement of efficient exchanges, by permitting the parties to effectively pre-commit to future cooperative behavior. Mutual pre-commitments can produce the efficient cooperate-cooperate equilibrium. The existence of contract law then tends to foster efficient cooperative behaviour. Institutions are considered to provide the mechanisms by which individuals can resolve social dilemmas [Steins (1999)]. They are sets of rules that people have created in order to control/regulate the behavior of people using a natural resource. Several layers of institutions are important for institutional development and economic performance. These layers, from the slowest moving to the fastest moving are: human motivations and social institutions, political institutions, legal institutions and private institutions [Azfar (2006)]. Institutions perform their role to frame rules, procedure and enabling environment for implementation of rules. Rights of individuals are recognised and recognised through institutions as well.